2004
DOI: 10.1097/00124784-200405000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Partnerships at the State Level

Abstract: Reforms in the public health infrastructure such as those called for in recent Institute of Medicine reports require stakeholder engagement on different levels than traditional grass-roots community work. The Turning Point Initiative, funded by The Robert Wood Johnson Foundation, involves 21 state-wide partnerships established for systems change and focused in specific areas of public health innovation and policy development. These partnerships represent a different model of strategic alliances and relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“… 2 Second, research has shown that institutions with women leaders are more likely to work collaboratively with others, which has been found to be vital for governmental public health agencies. 11 13 …”
mentioning
confidence: 99%
“… 2 Second, research has shown that institutions with women leaders are more likely to work collaboratively with others, which has been found to be vital for governmental public health agencies. 11 13 …”
mentioning
confidence: 99%
“…The readiness assessment also highlighted that current and existing TPP efforts were fragmented and could benefit from a unified leadership structure. A clear leadership structure is critical for partnerships to function well [16,17]. To ensure that efforts were aligned and unified, Youth First developed and implemented strategies to promote local leadership and build community infrastructure to support collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Collaboratives use different tactics and activities in varying degrees to advance their agendas. These tactics and activities serve multiple purposes: 1) elicit local knowledge to inform the design and implementation of strategies; 2) motivate core partners and the broader community of practitioners and citizens to get involved; 3) raise awareness about the problems being addressed and the need for change at multiple levels; and 4) align group-specific political and policy priorities (19,30,31). Needs assessments are unique in their ability to engage partners, policy makers, elected officials, media, and community members in agenda-setting and planning processes and create community awareness and buy-in (32,33).…”
Section: Discussionmentioning
confidence: 99%